2009
DOI: 10.1148/radiol.2501080833
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Iso-osmolar Iodixanol Compared with Nonionic Low-osmolar Contrast Media: Meta-analysis of Randomized Controlled Trials

Abstract: Iodixanol is not associated with a significantly reduced risk of CIN compared with the LOCM pooled together. However, in patients with intraarterial administration and renal insufficiency, iodixanol is associated with a reduced risk of CIN compared with iohexol, whereas no significant difference between iodixanol and other LOCM could be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(184 citation statements)
references
References 73 publications
6
173
0
5
Order By: Relevance
“…19 Since then, several larger randomized trials have been published that reported no difference in CIN when iodixanol was compared with various other low-osmolar contrast media (LOCM). 19,[121][122][123] 124,125 ), but no difference was noted in comparisons of iodixanol with iopamidol, iopromide, or ioversal, 124 and a single trial favored iomeprol. 123 A pooled comparison of iodixanol with all nonionic LOCM other than iohexol indicated equivalent safety (RR 0.97; CI 0.72 to 1.32, P¼ 0.86 125 ).…”
Section: Recommendation For Angiography In Patients With Chronic Kidnmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Since then, several larger randomized trials have been published that reported no difference in CIN when iodixanol was compared with various other low-osmolar contrast media (LOCM). 19,[121][122][123] 124,125 ), but no difference was noted in comparisons of iodixanol with iopamidol, iopromide, or ioversal, 124 and a single trial favored iomeprol. 123 A pooled comparison of iodixanol with all nonionic LOCM other than iohexol indicated equivalent safety (RR 0.97; CI 0.72 to 1.32, P¼ 0.86 125 ).…”
Section: Recommendation For Angiography In Patients With Chronic Kidnmentioning
confidence: 99%
“…19,[121][122][123] 124,125 ), but no difference was noted in comparisons of iodixanol with iopamidol, iopromide, or ioversal, 124 and a single trial favored iomeprol. 123 A pooled comparison of iodixanol with all nonionic LOCM other than iohexol indicated equivalent safety (RR 0.97; CI 0.72 to 1.32, P¼ 0.86 125 ). Results were consistent regardless of ancillary preventive therapies (hydration, acetylcysteine), route of administration (intravenous or intra-arterial), age, sex, dose, or preexisting CKD or diabetes.…”
Section: Recommendation For Angiography In Patients With Chronic Kidnmentioning
confidence: 99%
“…However, in a multicenter, randomized, double-blind comparison of the low-osmolar contrast medium (iopamidol) and the isoosmolar contrast medium (iodixanol), the incidence of CIN was not statistically different after the intra-arterial administration of iopamidol or iodixanol to high-risk patients [56]. In a meta-analysis of 25 RCTs, iso-osmolar iodixanol did not significantly reduce the risk of CIN (relative risk [RR] 0.80, 95 % CI 0.61-1.04) [57]. However, in patients with intra-arterial administration and kidney dysfunction, the risk of CIN was lower for isoosmolar iodixanol than for low-osmolar iohexol (RR 0.38, 95 % CI 0.21-0.68), whereas there was no difference between iodixanol and the other (non-iohexol) lowosmolar contrast media (RR 0.95, 95 % CI 0.50-1.78).…”
Section: Level Of Evidence: II Grade Of Recommendation: Not Applicablmentioning
confidence: 99%
“…The disparate results of these previous 14 clinical trials led to a proliferation of systematic reviews and meta-analyses comparing the nephrotoxicity of IOCM iodixanol and various LOCM; five of which have now been published [32,[62][63][64][65][66] . Among earlier meta-analyses by McCullough et al [62] , pooled data from 2727 patients from 16 doubleblind, RCTs have indicated that use of the IOCM iodixanol is associated with smaller rises in creatinine and lower rates of RCIN than LOCM (1.4% vs 3.5%, P < 0.001), especially in patients with CKD or CKD and diabetes mellitus.…”
Section: Type Of Contrast Agentsmentioning
confidence: 99%